The Role of Music Activities in Improving the Self-worth of the Elderly - Li, Jinyang (International Journal of Social Sciences and Public Administration, 2024)
Under current circumstances, the elderly's demand for elderly care is increasing, and the demand for elderly care services is becoming more diversified and personalized. On the basis of "elderly care", they need "elderly income" and "elderly reliance". Participating in music activities can enable the elderly to change from passively accepting elderly care services to actively obtaining elderly care services. This paper mainly reviews the current research results based on the literature with elderly care and music as keywords, and explores the mechanism and effect of music activities on the self-worth of the elderly in terms of music therapy and social enhancement, and makes a prospect for active elderly care behavior based on participating in music activities.